A Study on Social Media’s Impact among Midwifery Students : Framing The Midwifery Profession in The Digital Era - Fitria, Henni; Rusdi, Annisa; Yulizawati (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
One of the key pillars of maternal and child health services is the midwifery profession, particularly in efforts to reduce maternal and infant mortality. However, in the globalized era, the challenges faced by midwives are more than just clinical skills, but also how the profession is portrayed and perceived by society, especially by the next generation of midwives. The aim of this research is to investigate at how utilizing social media affects how undergraduate students see midwifery as a profession. A correlational quantitative study was conducted involving 144 midwifery students from the Faculty of Medicine, Andalas University. We used proportionate stratified random sampling to choose the participants. Structured questionnaires were used to gather information about how people use social media and what they think about the midwifery profession. After checking that the data was normal, a Pearson correlation analysis was done. The findings demonstrated that most people had a positive opinion of the midwifery profession (mean = 29.84, SD = 3.10) and were highly interested in professional content on social media (mean = 26.10, SD = 3.20). YouTube, Instagram, and TikTok were the most visited websites. Social media use was strongly positively correlated with how others perceived your professional image (r = 0.548, p < 0.001). Social media has a major effect on how midwifery students see themselves as professionals. Adding digital professionalism and media literacy to the midwifery curriculum is important for helping people learn how to use digital tools in a responsible and moral way.